Health Systems and Their Assessment: A Methodological Proposal of the Synthetic Outcome Measure - Piotr Romaniuk; Krzysztof Kaczmarek; Magdalena Syrkiewicz-Świtała; Tomasz Holecki; Adam R. Szromek (Frontiers Media S.A., 2018)
The effectiveness of health systems is an area of constant interest for public health researchers and practitioners. The varied approach to effectiveness itself has resulted in numerous methodological proposals related to its measurement. The limitations of the currently used methods lead to a constant search for better tools for the assessment of health systems. This article shows the possibilities of using the health system synthetic outcome measure (SOM) for this purpose. It is an original tool using 41 indicators referring to the epidemiological situation, health behaviors, and factors related to the health-care system, which allows a relatively quick and easy assessment of the health system in terms of its effectiveness. Construction of the measure of health system functioning in such a way allowed its presentation in dynamic perspective, i.e., assessing not only the health system itself in a given moment of time but also changes in the value of the effectiveness measures. In order to demonstrate the cognitive value of the SOM, the analysis of the effectiveness of health systems in 21 countries of Central and Eastern Europe during the transformation period was carried out. The mean SOM values calculated on the basis of the component measures allowed to differentiate countries in terms of the effectiveness of their health systems. Considering the whole period, a similar level of health system effects can be observed in Slovenia, Croatia, Czech Republic, Slovakia, Poland, Macedonia, and Albania. In the middle group, Hungary, Romania, Latvia, Lithuania, Georgia, Estonia, Bulgaria, Belarus, and Armenia were found. The third group, weakest in terms of achieved effects, was formed by health systems in countries like Ukraine, Moldova, and Russia. The presented method allows for the analysis of the health system outcomes from a comparative angle, eliminating arbitrariness of pinpointing a model solution as a potential reference point in the assessment of the systems. The measure, with the use of additional statistical tools to establish correlations with elements of the external and internal environment of a health system, allows for conducting analyses of conditions for differences in the effects of health system operation and circumstances for the effectiveness of reform processes.